2016
DOI: 10.1021/acscentsci.6b00176
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Activation of Supported Metathesis Catalysts by Organosilicon Reducing Agents

Abstract: Alkene metathesis is a widely and increasingly used reaction in academia and industry because of its efficiency in terms of atom economy and its wide applicability. This reaction is notably responsible for the production of several million tons of propene annually. Such industrial processes rely on inexpensive silica-supported tungsten oxide catalysts, which operate at high temperatures (>350 °C), in contrast with the mild room temperature reaction conditions typically used with the corresponding molecular alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(125 citation statements)
references
References 43 publications
4
118
0
3
Order By: Relevance
“…Mashima and Tsurugi have shown that 1 reduces binary W and Ti chlorides to lower oxidation states by chloride abstraction, a conversion which is perhaps even superior to using elemental Zn or Mg toward the same end. While it was originally envisioned that elimination of (Me 3 Si) 2 O from MO n by 1 might be a useful approach to MO n −1 , a recent application to support‐bound WO 3 gave instead tetravalent tungsten silyl esters, which is still a valuable 2 electron reduction, but without full elimination of W/O bonds and creation of lower metal coordination number . The method has also been applied to nanoparticle formation, silylation of B−F bonds and of α‐halo carbonyls, and deoxygenation of nitro compounds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mashima and Tsurugi have shown that 1 reduces binary W and Ti chlorides to lower oxidation states by chloride abstraction, a conversion which is perhaps even superior to using elemental Zn or Mg toward the same end. While it was originally envisioned that elimination of (Me 3 Si) 2 O from MO n by 1 might be a useful approach to MO n −1 , a recent application to support‐bound WO 3 gave instead tetravalent tungsten silyl esters, which is still a valuable 2 electron reduction, but without full elimination of W/O bonds and creation of lower metal coordination number . The method has also been applied to nanoparticle formation, silylation of B−F bonds and of α‐halo carbonyls, and deoxygenation of nitro compounds .…”
Section: Introductionmentioning
confidence: 99%
“…The method has also been applied to nanoparticle formation, silylation of B−F bonds and of α‐halo carbonyls, and deoxygenation of nitro compounds . In summary, the strengths and limitations of this attractive reagent are only just emerging …”
Section: Introductionmentioning
confidence: 99%
“…0.8 surface silanol per nm 2 ), 25 the unique magnetic properties of Dy(III) ions 26 —a Kramers ion with a large moment and often exhibiting a significant magnetic anisotropy—and the thermolytic molecular precursor approach, which allows clean removal of organic ligands and generation of isolated metal ions in an anisotropic environment provided by the surface. 2731 …”
mentioning
confidence: 99%
“…[527][528][529][530][531][532] Theses ystems andt heir possible activation pathways have recently been discussedi nd etail. [567] [224,225,[533][534][535][536][537][538][539][540] An alternative strategyh as focusedo nt he direct graftingo fm oleculara lkylidenec omplexes onto thes urface of oxides upports.…”
Section: Surface Sites In Industrial Catalystsmentioning
confidence: 99%
“…b) SP metallacycle formed in the reaction of (SiO)W(=O)(=CH-CMe 2 Ph)(dAdPO) with 13 C-labeled ethylene. [567] More than half of the W VI -oxo sites are reduced to W IV (along with trace amounts of W V )after activation with Me 4 -BTDP at 70 8 8C( Scheme 44 a). d) Silica-supported W-oxo-alkylidenes containing strongly s-donating ligands.…”
Section: Well-defined Silica-supported W-oxo-alkylidenesmentioning
confidence: 99%